2016
DOI: 10.1158/0008-5472.can-16-0136
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Implicating Immunological Host Effects in the Efficacy of Metronomic Low-Dose Chemotherapy

Abstract: Conventional chemotherapy drugs administered at a maximum tolerated dose (MTD) remains the backbone for treating most cancers. Low-dose metronomic (LDM) chemotherapy, which utilizes lower, less toxic, doses given on a close regular basis over prolonged periods, is an alternative and better tolerated potential strategy to improve chemotherapy. LDM chemotherapy has been evaluated preclinically and clinically and has shown therapeutic benefit, in both early and advanced stage metastatic disease, especially when u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 39 publications
5
46
0
Order By: Relevance
“…Thus, the patients with metronomic UFUR might have lower disease burden when cancer relapse. This is compatible with the finding reported Shaked et al[18] They found oral daily metronomic chemotherapy, using cyclophosphamide and UFT, had high anti-metastatic effect. They also found that low dose metronomic chemotherapy, compared with maximum tolerated dose, had better therapeutic advantage on advanced metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the patients with metronomic UFUR might have lower disease burden when cancer relapse. This is compatible with the finding reported Shaked et al[18] They found oral daily metronomic chemotherapy, using cyclophosphamide and UFT, had high anti-metastatic effect. They also found that low dose metronomic chemotherapy, compared with maximum tolerated dose, had better therapeutic advantage on advanced metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
“…Balb/c mice were treated with bortezomib or vehicle control, and after 24 hours, BM cells were flushed from femurs and tibia. The cells were immunostained with a mixture of metal-tagged antibodies (listed in Supplementary Table S2), and were used as previously described (17). The analysis of data were performed using Cytobank database (with viSNE algorithm), as previously described (18), when gating on CD45 þ cells.…”
Section: Mass Cytometry (Cytof)mentioning
confidence: 99%
“…The VEGF (-634CC) genotype was significantly associated with a shorter progression free survival. Genetic heterogeneity may not only affect the antivascular but also the immunomodulatory activities of MC [60]. …”
Section: Mechanisms Of Resistance To Metronomic Chemotherapymentioning
confidence: 99%